The Top End Sleepiness Scale (TESS): A New Tool to Assess Subjective Daytime Sleepiness Among Indigenous Australian Adults - Benn E (Dove Medical Press, 2021)
Edmund Benn,1 Hugh Wirth,1 Teagan Short,1 Timothy Howarth,2,3 Subash S Heraganahally1,3,4 1College of Medicine and Public Health, Flinders University, Adelaide, South Australia, Australia; 2College of Health and Human Sciences, Charles Darwin University, Darwin, Northern Territory, Australia; 3Darwin Respiratory and Sleep Health, Darwin Private Hospital, Darwin, Northern Territory, Australia; 4Department of Respiratory and Sleep Medicine, Royal Darwin Hospital, Darwin, Northern Territory, AustraliaCorrespondence: Subash S HeraganahallyDepartment of Respiratory and Sleep Medicine, Royal Darwin Hospital, Tiwi, Darwin, NT, AustraliaTel +61-8-89228888Fax +61-8-89206309Email hssubhashcmc@hotmail.comPurpose: To illustrate the utility of a newly developed culturally safe and clinically relevant subjective daytime sleepiness assessment tool “Top End Sleepiness Scale” (TESS) for use among Indigenous Australians.Patients and Methods: The TESS questionnaire consists of pictorial representations of 6 items representing daily activities that would induce daytime sleepiness specific for Indigenous Australians living in the regional and remote Australia. Consecutive adult Indigenous patients who consented to pilot the TESS questionnaire prior to undergoing a diagnostic polysomnography (PSG) at the Top End Health Service region, Northern Territory of Australia were assessed. The TESS questionnaire was evaluated for its correlation in predicting obstructive sleep apnea (OSA) according to apnea-hypopnea index.Results: Eighty-two patients were included. The majority (70%) had moderate to severe OSA (AHI ≥ 15). Patients were aged in their mid-40’s (45.47 95% CI (42.9, 48.05)) with a tendency to obesity (median BMI 33.67 IQR 30.86, 38.95) and a high prevalence of chronic conditions (72%) (hypertension, diabetes or heart disease). The TESS showed high internal consistency (Split half Spearman correlation=0.71, Cronbach’s α =0.81), and a cut-off value ≥ 3 resulted in sensitivity 84%, specificity 38%. Comparison of area under the curve for TESS to Epworth Sleepiness Scale (ESS) in this sample showed the TESS to have greater sensitivity and specificity overall, which approached significance (p=0.072) when cut-off values of ≥ 3 and ≥ 8 (TESS & ESS respectively) were used. The sensitivity and specificity for TESS was also comparable to the other currently used questionnaires, such as the Berlin Questionnaire, STOP-BANG and OSA 50.Conclusion: Currently, there are no subjective daytime sleepiness assessment toll available specifically for Indigenous population. The proposed TESS sleepiness screening tool represented in this study can potentially complement or adopted alongside other existing questionnaire, which may offer greater utility in the assessment of sleep disorders among Indigenous people.Keywords: First Nations, Aboriginal, Epworth Sleepiness Scale, indigenous, Sleepiness Scale, subjective daytime sleepiness